The effect of adding nitrogen and potassium to the soil and spraying on the accumulation Dry matter and nitrogen concentrations in shoots of wheat plant Triticum aestivum L (Journal of the College of Basic Education, 2023)
A field experiment was conducted in Ershadiyeh in a sedimentary soil with a mixture of clay and silty texture inthe winter season. 2005-2004 to determine the best concentration of nitrogen and potassium to spray onThe vegetation of the wheat plant, cultivar Ibaa 95 - in the two stages of inflorescence and flowering and complementaryof fertilization and their effect on dry matter accumulation and the percentage distribution of nitrogen concentration.in the shoot of wheat plants.A factorial experiment was carried out with a completely randomized block design, RCBD, which included fourThe concentration of nitrogen is 6000, 5000, 4000, 0} mg N.L-1 in the form of urea fertilizer(N% 46) {, and the four concentrations of potassium are 0, 500, 1000, 1500} mg K.L-1 in a formPotassium sulphate fertilizer {(K% 41.50) in addition to the traditional addition treatment to the soilAnd three microt. The results showed the superiority of foliar feeding with nitrogen and potassium fertilizers.Significantly increased the accumulation of dry matter and the percentage of nitrogen concentration in the totalThe vegetative growth of wheat compared to the treatment of conventional addition to the soil.